Diseño de una red de valor de ciclo cerrado para los residuos de Aparatos Electricos y Electronicos tipo III en Bogotá (2019)
The development and advancement of information and communication technologies, generate the production of different devices to meet different needs of humans, these devices are called Electrical Devices and electronics. At the end of their life cycle for different reasons such as disuse, quality, programmed obsolescence, etc., became Waste of Electrical and Electronic Devices, which without having an adequate final disposition affects the environment and human health among other consequences negative According to the classification of the European Union the WEEE type III that properly all those computer and telecommunications equipment such as desktop computers laptops, landlines and cell phones, among other devices, they are one of the categories of WEEE that are most consumed worldwide, a national level identifies Bogotá as one of the cities with the highest consumption of technology and in turn of Electrical and Electronic Devices. The implementation of a closed cycle value network, where they are define agents, actuators and aligned processes and with this achieve the design of a closed cycle value network for waste of electrical and electronic equipment type III for the city of Bogotá.